Reproductive pathophysiology of non-pregnant does challenged with Mannheimia haemolytica serotype A2 and its outer membrane protein extract - Abdirahman, Boorei Mohamed (2021)
Mannheimia haemolytica causes pneumonic pasteurellosis (mannheimiosis) which is a common respiratory disease in goats and sheep causing huge economic losses to farmers around the world. In Malaysia, the primary causative agent for small ruminants’ pneumonic mannheimiosis is M. haemolytica serotype A2. The major virulence factors involved in the pathogenesis of pneumonic mannheimiosis are lipopolysaccharide (LPS) and outer membrane protein (OMP). Most of the previous studies were focused on the pathophysiology of the respiratory system in pneumonic goats due to M. haemolytica. It remains unclear whether M. haemolytica has effects on the female reproductive system. Hence, this study was intended to determine the concentration of reproductive hormones (oestrogen and progesterone), pro-inflammatory cytokines (interleukin-1β and interleukin-6), acute phase proteins (haptoglobin and serum amyloid A) and clinical response changes in female goats after challenge with M. haemolytica A2 and its outer membrane protein (OMP). In this study, 12 clinically healthy non-pregnant, cross bred does were used and divided equally into three groups. Does in group 1 (control group) were challenged with 2 ml of sterile phosphate buffered saline (PBS) intranasally, and group 2 does were challenged intranasally with 2 ml of suspension containing 109 colony forming unit (cfu) of M. haemolytica A2. Does in group 3 were challenged with 2ml of OMP intramuscularly extracted from 109 cfu of M. haemolytica A2. Clinical responses were observed following the challenge and blood samples were collected at (0, 1, 2, 4, 6, 12 and 24 hours and at day 3, 7, 21, 35 and 56) post-inoculation for determination of (IL-1β, IL-6, Hp, SAA, oestrogen and progesterone) with sandwich ELISA. The challenged groups showed significant differences (p < 0.05) in rectal temperature, respiratory rate, heart rate and rumen motility compared to the control group. The results of serum analyses revealed that the concentrations of progesterone and oestrogen were significantly decreased (p < 0.05), while the concentrations of pro-inflammatory cytokines (IL-1β and IL-6) and acute phase proteins (Hp and SAA) were significantly increased (p < 0.05) in the challenged groups compared to the control group. The results of histopathological lesions in the lungs, liver, lymph nodes and the reproductive organs revealed mild to moderate significant change (p < 0.05) in both treatment groups compared to the control group. Therefore, these findings suggest that M. haemolytica serotype A2 and its OMP potentially contribute to infertility in female goats and responsible for the occurrence of hormonal imbalances which in turn leads to reproductive inefficiency.